Serum heat shock protein 90 as a future predictive biomarker in childhood acute lymphoblastic leukemia - Pawlik-Gwozdecka, Dorota (Cent Eur J Immunol, 2020)
Heat shock proteins (HSPs) attract the attention of scientists and clinicians due to their potential role as diagnostic and prognostic factors in a variety of cancers. HSP90 is one of the most important and well-known family members, necessary for maintaining intracellular homeostasis. In the extracellular space, it is responsible for the transmission of alarm signals to the immune system. Numerous reports have indicated that the level of intra - and extracellular HSP90 can correlate either with a poorer prognosis or with a better outcome, depending on the type of cancer. Still, little is known why the level of this chaperone is increased in some tumors and decreased in others, reflecting dual role of protein in cell death processes. Currently, there is no database reporting levels of serum HSP90 in children with acute lymphoblastic leukemia (ALL). As such, using enzyme-linked immunosorbent assay (ELISA) method, we aimed to determine this parameter in a group of 21 patients with newly diagnosed ALL. We found decreased protein serum levels in patients at disease presentation and after induction block of chemotherapy in comparison to healthy controls. Furthermore, we observed a negative correlation between HSP90 serum levels and one of the earliest prognostic factors of the treatment response – peripheral blood lymphoblasts on the 8(th) day of treatment. Our results indicate that HSP90 serum may play an important role in leukemogenesis and could be used as a marker to predict treatment failure in children with ALL.